Splątane światy literatury i filmu - Krajewska, Anna (Przestrzenie Teorii, 2019)
Krajewska Anna, Splątane światy literatury i filmu [The Entangled Worlds of Literature and Film]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 7–12. ISSN 1644-6763. DOI 10.14746/pt.2019.32.0. In view of the relations between literature and film, the article contains suggestions for ways to use performative approaches, which preclude concepts of adaptation, in favour of processes defining actions involving the entanglement of the arts.